Tuning the work function of monolayer graphene on 4H-SiC (0001) with nitric acid. (12th October 2015) - Günes, Fethullah; Arezki, Hakim; Pierucci, Debora; Alamarguy, David; Alvarez, José; Kleider, Jean-Paul; Dappe, Yannick J; Ouerghi, Abdelkarim; Boutchich, Mohamed
Abstract: Chemical doping of graphene is a key process for the modulation of its electronic properties and the design and fabrication of graphene-based nanoelectronic devices. Here, we study the adsorption of diluted concentrations of nitric acid (HNO3 ) onto monolayer graphene/4H-SiC (0001) to induce a variation of the graphene work function (WF). Raman spectroscopy indicates an increase in the defect density subsequent to the doping. Moreover, ultraviolet photoemission spectroscopy (UPS) was utilized to quantify the WF shift. UPS data show that the WF of the graphene layer decreased from 4.3 eV (pristine) down to 3.8 eV (30% HNO3 ) and then increased to 4.4 eV at 100% HNO3 concentration. These observations were confirmed using density functional theory (DFT) calculations. This straightforward process allows a large WF modulation, rendering the molecularly modified graphene/4H-SiC(0001) a highly suitable electron or hole injection electrode.